(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2023)
The Coronavirus disease 2019 (COVID-19) re-shaped patient care in the United States beginning in March 2020. While fear of contracting the virus was prominent within the general population, hospitals also prioritized surges of COVID-19 patients by canceling in-person clinic appointments, clinical trials, and elective surgeries. To evaluate the state of clinical practice during the first wave of COVID-19, a regional survey was conducted of clinicians from the University of Toledo Medical Center (UTMC) and ProMedica Toledo hospitals and area clinics from March 9 to July 31, 2020. Qualitative free-form responses from clinicians indicated that both hospital systems observed decreases in patient loads and canceled clinics. We then evaluated how COVID-19 impacted workload in specialty clinics specifically within UTMC. Clinical productivity changes were quantified by evaluating Work Relative Value Units (wRVUs) for UTMC clinics. wRVUs compared to the same period in 2019 revealed the pandemic’s effects of suppressing wRVU in nearly all clinics examined in the initial stages of the first wave. wRVUs recovered to 2019 levels in most specialties and even surpassed 2019 levels by the end of the first wave of the pandemic. The recovery of wRVUs within specialty care during the first wave of the COVID-19 pandemic reveals the adaptability of the UTMC medical system in Northwest Ohio for navigating a rapidly changing infectious disease landscape.